An efficient method to sample Musca domestica (Linnaeus, 1758) (Diptera: Muscidae) using coloured pan-traps in a cage poultry facility - Bianca P. Valério; Bruno S. Nunes; Thiago M. Alvarenga; César F. Carvalho; Leopoldo F. O. Bernardi; Stephan M. Carvalho; Lívia M. S. Ataíde (Entomological Communications, 2023)
When houseflies find optimal conditions to develop, they rapidly increase their population size negatively impacting both humans and animals through nuisance and the transmission of pathogens. Musca domestica Linnaeus, 1758 (Diptera: Muscidae) shows a preference for animal faeces and for this reason it is a serious pest in animal breeding facilities. To prevent proliferation of houseflies and to evaluate the efficiency of the control methods, it is important to routinely monitor the activity of this dipteran in such facilities. There are several types of traps for sampling houseflies in breeding sites, here we used colored pan-traps to evaluate the efficiency of the trap and its color in sampling M. domestica in a cage poultry facility located in the city of Nepomuceno, Minas Gerais, Brazil. To do so, we set up yellow, white, blue and red pan-traps next to the cages of poultries and collected flies once a week for a period of a year. Although the density of M. domestica was high during the entire period of sampling, more flies were collected in white (monthly average of 470.83 flies) than in yellow (327.55), blue (267.14) and red traps (199.63). Hence, we argue that this poultry farm needs to improve its housefly monitoring program and we suggest a continuous use of white pan-traps to monitor the efficiency of the pest control methods implemented in the facility.